2010
DOI: 10.1364/oe.18.002695
|View full text |Cite
|
Sign up to set email alerts
|

Exploring, tailoring, and traversing the solution landscape of a phase-shaped CARS process

Abstract: Pulse shaping techniques are used to improve the selectivity of broadband CARS experiments, and to reject the overwhelming background. Knowledge about the fitness landscape and the capability of tailoring it is crucial for both fundamental insight and performing an efficient optimization of phase shapes. We use an evolutionary algorithm to find the optimal spectral phase of the broadband pump and probe beams in a background-suppressed shaped CARS process. We then investigate the shapes, symmetries, and topolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…The present diagram may be extended to include more elaborate pulse sequences 20 as well as pulse shaping effects. 21 We have shown that electronically off resonant stimulated Raman measurements cannot possess both high temporal and spectral resolution, beyond the transform limit. The signal is determined by the evolution during a single time interval, representing backward propagation from t to T .…”
mentioning
confidence: 99%
“…The present diagram may be extended to include more elaborate pulse sequences 20 as well as pulse shaping effects. 21 We have shown that electronically off resonant stimulated Raman measurements cannot possess both high temporal and spectral resolution, beyond the transform limit. The signal is determined by the evolution during a single time interval, representing backward propagation from t to T .…”
mentioning
confidence: 99%
“…Various methods developed so far include exploiting the polarization dependences of the resonant and nonresonant components of χ (3) [1][2][3][4][5], directly measuring [6][7][8] or extracting [9][10][11] the vibrational phase of the oscillators, shaping the phase of a broadband optical pulse to match that of the molecule [12][13][14][15], or introducing temporal delays to probe the resonant vibrational state after the nonresonant coherence has decayed [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a strong, frequencyindependent non-resonant background interferes with the resonant signal of interest, reducing contrast and creating imaging and spectral artifacts that can be difficult to interpret. In order to remove, suppress, or extract this non-resonant background, a number of specialized methods have been developed that exploit polarization [9,13,14], spectral [15], time [16][17][18], and/or phase [19][20][21] dependencies of the CARS process. This last feature is of particular interest because it can be used to determine the full complex vibrational response of an arbitrary sample [22].…”
mentioning
confidence: 99%